The Effect Of Green Recruitment And Green Compensation On Green Performance - Farhana Hasmin; Idayanti Nursyamsi; Krishna Ilyas; Imam Santoso (International Journal of Economics, Business and Innovation Research, 2025)
The research aims to analyze the impact of green recruitment and green compensation on the green performance of employees serving in the office of the Governor of West Sulawesi. The data in this research was collected from employees/employees who were willing to participate as respondents. This research uses primary data by conducting a direct survey in the field via questionnaires to 57 respondents. The data analysis method used is multiple linear regression analysis. The research results show that, partially, the green recruitment and green compensation variables have a positive and significant influence on green performance.